Photocatalytic Activity and Antibacterial Effect of Ag3PO4 Powders Against Methicillin-resistant Staphylococcus aureus - Botelho, Gleice; de Foggi, Camila Cristina; Vergani, Carlos Eduardo; Pereira, Wyllamanney Silva; dos Santos Júnior, Ricardo Kaminishi; Longo, Elson (Orbital: The Electronic Journal of Chemistry, 2021)
In this study, silver phosphate (Ag3PO4) was successfully prepared through a simple precipitation method, and its structural, optical, and morphological properties were characterized by X-ray diffraction, Rietveld refinement, Fourier transform infrared spectroscopy, UV–vis diffuse reflectance spectroscopy, photoluminescence measurements, and field emission scanning electron microscopy (FE-SEM). Thereafter, the photocatalytic activity for the degradation of rhodamine B (RhB) dye and the antibacterial effect against methicillin-resistant Staphylococcus aureus (MRSA) were analyzed. Ag3PO4 was highly photocatalytic, degrading approximately 100% of the RhB after 25 min of visible light exposure. The photocatalytic mechanism was evaluated by trapping experiments indicating that photogenerated holes and superoxide radicals were the principal species present in the photocatalytic system. In addition, Ag3PO4 is a potential bacterial agent as it reduced the MRSA population even at sub-inhibitory concentrations. Morphological changes of the MRSA cells exposed to Ag3PO4 powder were investigated by the FE-SEM analysis, and a possible mechanism involving the release of dissolved Ag+, together with the production of reactive photocatalytic oxygen species is proposed based on the experimental results. DOI: http://dx.doi.org/10.17807/orbital.v13i3.1567